Sensitive sucrose biosensors with high Q factors empowered by quasi-bound states in the continuum in compound grating waveguide structures - Feng Wu; Dejun Liu; Xi Yu (Results in Physics, 2023)
As a special kind of localized states, bound states in the continuum (BICs) have been widely utilized to design high-performance lasers, absorbers, and biosensors. In this paper, we realize a BIC in a compound grating waveguide structure based on the switchable guided resonance. Empowered by the ultra-strong resonance strength of the quasi-BIC, we theoretically achieve sensitive sucrose biosensing with a high Q factor. The minimum resolution of the sucrose concentration is 1.59 × 10-5 g/mL and the maximum Q factor reaches 7311. Our work not only provides a competitive mechanism to design high-performance sucrose biosensors, but also promotes the development of sucrose biosensors in biology, chemistry, and medical science.